BRIDGING BUSINESS-EDUCATION GAPS: INSTRUCTIONAL DESIGN OF ENTREPRENEUR COURSE AND ITS MICRO-CREDENTIAL CERTIFICATION FRAMEWORK FOR SELF-EMPLOYED JUNIOR BUSINESS FACILITATOR OUTCOME - Surono, Surono (International Journal of Social Service and Research, 2024)
Micro-Credential Certification Schemes are increasingly essential in business management education for several reasons, including flexibility, relevance to industry trends, recognition of skills, modular learning, and career development. The research aims to develop a comprehensive micro-credential certification framework that aligns with national standards, business technical standards, and regulations, addressing the need for industry-recognized certifications. Furthermore, the research focuses on developing a Semester Learning Plan (SLP) based on the Integrated Certification Scheme and the instructional design, ensuring a cohesive and comprehensive approach to learning and certification. The R&D method is selected to systematically develop and refine an instructional design that harmonizes with this certification system. The data analysis will involve qualitative analysis using thematic analysis to identify key themes and patterns from interviews, observations, and document reviews, which will help assess the strengths and weaknesses of the educational program and the certification scheme. The formative evaluation results of students participating in the entrepreneurship program totaling 74 students will be used to evaluate the perceived value of the certification framework. The integration of the micro credential certification with instructional design has also proven effective in enhancing graduates' competitiveness in the job market, supporting career development through modular learning that is aligned with industry trends.